2007
DOI: 10.1158/1078-0432.ccr-06-1387
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Signal Transducers and Activators of Transcription 1 and 3 Signaling in Melanoma by High-Dose IFNα2b

Abstract: Purpose: The Janus-activated kinase/signal transducers and activators of transcription (STAT) pathway of IFN signaling is important to immunoregulation and tumor progression. STAT1plays a prominent role in the effector immune response, whereas STAT3 is implicated in tumor progression and down-regulation of the response to type IIFNs.The goal of this study was to understand the effects of high-dose IFNa2b (HDI) in relation to the balance of pSTAT1and pSTAT3. Experimental Design: We evaluated STAT1 and STAT3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 52 publications
5
84
1
Order By: Relevance
“…As evidence accumulating in mouse models that inhibiting Stat3 can boost the efficacies of immunotherapy, supporting data from clinical trials are also emerging. A recent study of prospective neoadjuvant trial of interferon-α therapy suggests that higher phosphorylated Stat1 (pStat1) over phosphorylated Stat3 in both tumor cells and lymphocytes pretreatment were associated with longer overall survival [49]. In addition, high density interferon-α treatment is associated with upregulation of pStat1 and down-regulation of pStat3 [49].…”
Section: Evidence Of Stat3 As An Important Target For Cancer Immunothmentioning
confidence: 99%
See 1 more Smart Citation
“…As evidence accumulating in mouse models that inhibiting Stat3 can boost the efficacies of immunotherapy, supporting data from clinical trials are also emerging. A recent study of prospective neoadjuvant trial of interferon-α therapy suggests that higher phosphorylated Stat1 (pStat1) over phosphorylated Stat3 in both tumor cells and lymphocytes pretreatment were associated with longer overall survival [49]. In addition, high density interferon-α treatment is associated with upregulation of pStat1 and down-regulation of pStat3 [49].…”
Section: Evidence Of Stat3 As An Important Target For Cancer Immunothmentioning
confidence: 99%
“…A recent study of prospective neoadjuvant trial of interferon-α therapy suggests that higher phosphorylated Stat1 (pStat1) over phosphorylated Stat3 in both tumor cells and lymphocytes pretreatment were associated with longer overall survival [49]. In addition, high density interferon-α treatment is associated with upregulation of pStat1 and down-regulation of pStat3 [49]. These data suggest that the ratio between pStat1/pStat3 at the baseline could serve as a predictor of clinical outcome of certain immunotherapies and that increasing this ratio may tip the balance towards better immunotherapeutic effects.…”
Section: Evidence Of Stat3 As An Important Target For Cancer Immunothmentioning
confidence: 99%
“…In contrast, the lethal Py17XL infection induced a pSTAT3-dominant response during the whole short course with the death of the animals. The pSTAT1/pSTAT3 ratio has been evaluated as an important index for immunoregulation (26,31,35,36), so we analyzed the constituent ratio of pSTAT1 and pSTAT3 in the spleen during the whole course of Py17XNL ( Figure 2G) or Py17XL ( Figure 2H) infection. The pSTAT1/pSTAT3 ratio was increased during the early stage of Py17XNL infection, peaked on day 7 p.i., and subsequently decreased.…”
Section: Dynamic Analysis Of Pstat1 and Pstat3 Levels In Mice Infectementioning
confidence: 99%
“…So the balance of pSTAT1 and pSTAT3, which has been studied in cancer immunity (31,34), has an important role in regulation of immune responses. A higher pSTAT1/pSTAT3 ratio in tumor cell or in immune cell is associated with longer survival for tumor patients (26,31,35,36). However, this balance has not been studied in malaria immunology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, antigen presentation to CD8 + CTL usually involves proteolytic cleavage of antigen in the cytosol and delivery of epitope peptides onto MHC class I molecules in the endoplasmic reticulum via the heterodimeric peptide transporter TAP1/TAP2. In a recent study, Wang et al demonstrated that IFN-alpha2b significantly modulates the balance of STAT1/STAT3 in tumor cells and host lymphocytes, leading to up-regulation of TAP2 and augmented host antitumor response [22]. Chemotherapy agents commonly used in cancer therapy, such as 5-fluorouracil, have also been shown to up-regulate CEA and MHC class I in tumor cells.…”
Section: Vaccine and Chemotherapymentioning
confidence: 99%